Population Fluctuation and Infestation Rates of Ceratitis capitata (Wiedemann) (Diptera: Tephritidae) on Different Pomegranate Varieties in Hatay (Turkey) - Nihat Demirel (Turkish Journal of Agriculture: Food Science and Technology)
The Mediterranean fruit fly (Medfly), Ceratitis capitata (Wiedemann) (Diptera: Tephritidae), is a serious pest on pomegranate in Turkey. The purpose of this study was to determine population fluctuation and infestation rates of medfly on various pomegranate varieties in Hatay province of Turkey. The Eostrap® invaginada traps baited with % 95 Trimedlure impregnated in a polymeric plug-type dispenser were used. The fruit infestation assessment was measured by a hundred fruits chosen randomly from ten trees in each of sampled orchard and checked for medfly punctures and infested fruits were counted. As a result of two-year investigations, this pest was found in six sites, which are located in Kırıkhan (Delibekirli, Kurtlu soğuksu) and Serinyol districts of Hatay province. In 2010, the highest mean of the catches per traps were recorded on 13 October (236.5), followed by 6 October (166.5), 29 September (145.5), 20 October (145.0) and 22 September (110.0) on ‘Karamehmet+katırbaşı’ varieties in Delibekirli village. Moreover, the highest mean of the catches per traps were recorded on 6 October (38.0), followed by 13 October (33.5), 20 October (17.0), 29 September (16) and 22 September (9) on ‘Katırbaşı’ varieties in Kurtlu soğuksu. In 2011, the highest mean of the catches per traps were recorded on 7 November (240.0), followed by 14 November (162.5), 31 October (100.5), 24 October (58) and 21 November (32) on Katırbaşı and Hicaz varieties of Serinyol district. The highest percentages of infestation rates were observed at orchard II (42) on ‘Karamehmet+katırbaşı’, followed orchard I (37) on ‘Karamehmet+katırbaşı’, orchard III (7) on ‘Katırbaşı’ and orchard IV (3) on ‘Katırbaşı’ varieties 2010. In addition, the highest percentages of infestation rates were observed at orchard I (44) on ‘Katırbaşı’, followed at orchard II (8) on ‘Hicaz’ varieties 2011. The highest mean of medfly was observed in October and September in 2010, and in November and October in 2011 due to ripening and harvesting time of fruits. The medfly caused significantly more infestation rates on ‘Karamehmet+katırbaşı’ and ‘Katırbaşı’ pomegranate than ‘Hicaz’ pomegranate.